Moving up the Energy Ladder: The Effect of an Increase in Economic Well-Being on the Fuel Consumption Choices of the Poor in India - Hanna, Rema; Oliva, Paulina (American Economic Review, 2015)
Rising household wealth may potentially impact both total fuel consumption and fuel-type composition, resulting in significant health and environmental implications. Using data from a field experiment in India, we explore the effects of a transfer program that provided poor, rural households with greater levels of assets and cash. Total fuel consumption rose as a result of the transfers. Households shifted from using electricity rather than kerosene as their primary form of light, but total kerosene consumption also rose. In contrast, we did not observe a shift to cleaner cooking fuels.